Development of E-LKPD Based on Problem Based Learning on Excretory System Material for High Schools - Angga Bagas Saputra; Afreni Hamidah; Raissa Mataniari (Jurnal Penelitian Pendidikan IPA, 2024)
Learning carried out using learning tools in the form of printed LKPD makes students easily bored. Lack of use of technology in learning also often makes students less motivated. Therefore, this research aims to develop more innovative learning tools and see their feasibility which will be validated by media experts and material experts. The product developed is a PBL-based E-LKPD on excretory system material. This research was carried out at the Madrasah Aliyah Laboratory in Jambi City. This research is development research (R&D) with the ADDIE development model. Data collection techniques use observation, interviews and documentation. The instruments used were questionnaires and teacher assessment sheets. The trial was carried out on 6 students and 15 students. Material validation was 87.5% in the "very good" category. The media validator assessment was 73.6% in the "very good" category. The biology teacher's assessment was 89.7% in the "very good" category so it can be tested on students. The small group's response was 81.8% in the "very good" category and the large group's response was 88% in the very good category. In this research, the implementation stage is just knowing the students' responses and it is hoped that implementation will be carried out in future research. Thus, it can be concluded that the development of E-LKPD based on Problem Based Learning on Excretory System Material for Class XI Students is suitable for use in the learning process.